Upaya Guru PAI Dalam Menanamkan Nilai-Nilai Pendidikan Karakter Islami Pada Peserta Didik - Rahmah, Rahmah; Maharani, Dewi (Prodi Pendidikan Keagamaan Islam, 2024)
Based on the research found, there is a uniqueness in changing the name of the school, which was previously called SMK Citra Bangsa to SMK Al-Aqsyar Islamic School Bogor in 2021 based on the wishes of the Am Badar Foundation, which aims to instill the shari'ah creed, which stands for